Efektivitas Metode Group Investigation (GI) Berbantuan Modul Terhadap Sikap Kebinekaan Global Siswa Pada Kurikulum Merdeka - Bernadeta Yulisa; Yustinus Joko Wahyu Yuniarto; Andarweni Astuti (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2023)
The tendency of students to form circles often causes conflict, lack of self-confidence, difficulty socializing, low learning outcomes, and intolerance. This study used a quantitative experimental research method. The research sample was students of class VII SMP Yohannes XXIII Semarang. The purpose of this study was conducted to determine the effect, increase in learning outcomes, and the effectiveness of using the module-assisted GI method on learning (PAK) on learning outcomes. The instrument used documentation, questionnaires, and tests. The results showed that the average pretest score was 39, posttest was 84, and the difference was 45. The average learning achievement exceeded KKM 78 with an increase in score reaching 1213. The results of global diversity attitudes and student achievement showed that by 87.3%. This means that the attitude of global diversity of students influences as much as 87.3%. The mean of the N-gain test is 76.2 which is in the very good and effective category. It can be concluded that the module-assisted GI method is effective in learning, able to increase: global diversity attitude values, learning outcomes, and is effective in increasing global diversity attitudes.